Buyers’ Perception towards Life Insurance Policies Offered in Insurance Industry: A Study - Ghai, R K; Vaish, Dolly (Management Journal for Advanced Research, 2022)
The aim of this paper is to examine the buyers’ perception towards life insurance policies offered by the public and the private sector organizations while focusing on some important factors viz. knowledge, information, awareness, literacy and views about life insurance policies among buyers. This paper is an attempt to investigate the overall perception of the life insurance buyers targeting pre and post buying behavior. This research study was surveyed on a variety of buyers of Indore city (Madhya Pradesh) based on various demographic factors. The research findings revealed that still people do not pay due importance to life insurance policy, they prefer other financial instruments, such as- bank deposit, mutual funds, stock market and some others. The study also found that the policies which are propagated by agents, and endorsed by organizations, have been in higher demand. The buyers treated life insurance as an investment and tax saving instrument instead of risk coverage instrument. The buyers have less knowledge, information and literacy about life insurance. The views of illiterate people were not contingent due to technical issues such as, physical absence of inquirers, language problem, pre-inquiry orientation, etc. If those were contingent to admit, the result would have been more valuable.